2021
DOI: 10.1016/j.rmed.2021.106552
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax and barotrauma in invasively ventilated patients with COVID-19

Abstract: We read with great interest the article by Chopra et al. recently published on Respiratory Medicine [1].In their multicenter study, the Authors present incidence, clinical characteristics and outcome of pneumothorax in critically ill patients with coronavirus disease 2019 . They found that pneumothorax rate among invasively ventilated COVID-19 patients is 80/594 (13 %), and mortality rate for patients who developed pneumothorax is 50/80 (62 %). On the contrary, among 160 randomly selected invasively ventilated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…A study investigating PTX alone in COVID-19 also found the incidence to be 0.56%. 15 The overall mortality of 52% from air leak, in our centre, is in line with some studies, 16 , 17 but higher that reported in others. 3 The mortality difference in our patients with and without air leak is not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…A study investigating PTX alone in COVID-19 also found the incidence to be 0.56%. 15 The overall mortality of 52% from air leak, in our centre, is in line with some studies, 16 , 17 but higher that reported in others. 3 The mortality difference in our patients with and without air leak is not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…These data are in line with those identified in our recent systematic review, which confirms a 61.6% pooled estimate for mortality in COVID-19 patients who develop barotrauma [ 10 , 11 ]. Of note, we observed that the overall rate of barotrauma is more frequent in COVID-19 patients, with 14.7% of the patients having at least one barotrauma event (pooled estimates, 16.1%; 95% confidence interval [CI], 11.8%–20.4%), whilst in non-COVID-19 ARDS patients, barotrauma occurred in 31/493 patients (6.3%; pooled estimates, 5.7%; 95% CI, −2.1%–13.5%) [ 10 ].…”
Section: Main Textsupporting
confidence: 91%
“…Patients on invasive mechanical ventilation were controlled by sedation, analgesia, and curarization when necessary, so that they could be optimally adapted to protective mechanical ventilation by choosing an optimal driving pressure and plateau pressure (≤14 cm H 2 O and ≤30 cm H 2 O, when it was possible) in order to reduce the risk of barotrauma [ 26 ]. This may be the reason why we have had a lower incidence in intubated patients than that documented in some other recent studies [ 27 , 28 ]. Furthermore, the incidence of barotrauma due to iatrogenic causes in the ICU (2.2%), mostly from thoracentesis and fibrobronchoscopy, was no higher than that documented in several studies [ 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 43%